Forward Guidance Through Interest Rate Projections: Does It Work? - Leif Brubakk; Hong Xu; Saskia ter Ellen (Norges Bank, 2017)
Based on high-frequency data for Norway and Sweden, we investigate to what extent explicit forward guidance from monetary policy makers, by means of publishing the path of expected future policy rates, affects the market yield curve. We summarise movements in the yield curve by two latent factors (the 'target factor' and 'market path factor'), which capture market participants' assessment of all relevant monetary policy communication made available on announcement days. We then show that information contained in the published interest rate path has a significant effect on the market path, and can explain up to 47% of the market path factor. Hence, we conclude that 'explicit' forward guidance in the form of publishing the interest rate path succeeds in moving markets in the desired direction. Furthermore, our results show that central bank and market revisions of interest rate expectations are strongly correlated. This suggests that market participants to a large extent understand the monetary policy reaction pattern.
hdl:11250/2495585
Keywords: E43; E44; E52; E58; G12; 330; monetary policy; forward guidance; interest rates